2018
DOI: 10.3390/s18114003
|View full text |Cite
|
Sign up to set email alerts
|

Quaternion-Based Local Frame Alignment between an Inertial Measurement Unit and a Motion Capture System

Abstract: Local frame alignment between an inertial measurement unit (IMU) system and an optical motion capture system (MCS) is necessary to combine the two systems for motion analysis and to validate the accuracy of IMU-based motion data by using references obtained through the MCS. In this study, we propose a new quaternion-based local frame alignment method where equations of angular velocity transformation are used to determine the frame alignment orientation in the form of quaternion. The performance of the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…For each subject, the misalignment was quantified around the axes of the cluster and was less than 1° around the X -axis, 26° around the Y -axis and 2° around the Z -axis. The literature (e.g., [16,54,55]) showed that the method proposed by de Vries enables an alignment with an error lower than 1°.…”
Section: Methodsmentioning
confidence: 99%
“…For each subject, the misalignment was quantified around the axes of the cluster and was less than 1° around the X -axis, 26° around the Y -axis and 2° around the Z -axis. The literature (e.g., [16,54,55]) showed that the method proposed by de Vries enables an alignment with an error lower than 1°.…”
Section: Methodsmentioning
confidence: 99%
“…Cuesta-Vargas et al [ 5 ] did an extensive literature review around works that “compare inertial sensors with any kind of gold standard”, indicating that “this gold standard has to be a tool for measuring human movement”. Lee and Jung [ 6 ] proposed a new method for local frame alignment between an IMU and a motion capture system, validating it with well-controlled experiments. Ricci et al [ 7 ] used a robotic arm and commercial IMUs to study movements related to “typical human dynamics”, and got errors of up to 10°, depending on the frequency, amplitude and orientation of the rotations.…”
Section: Related Workmentioning
confidence: 90%
“…However, the relative orientation between the actual coordinate system of the sensor and the local coordinate system of the rigid body obtained using the optical camera may increase the error when evaluating the accuracy of the orientation estimation. To align the two coordinate systems, the quaternion-based local frame alignment method proposed in [38] was used. The experiment was conducted by randomly shaking the sensor-attached rigid body by hand.…”
Section: Methodsmentioning
confidence: 99%